2016
DOI: 10.1144/sp441.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing tsunami hazard using heterogeneous slip models in the Mentawai Islands, Indonesia

Abstract: Tsunami hazard maps are generated for the coastline of the Mentawai Islands, West Sumatra, Indonesia, to support evacuation and disaster response planning. A random heterogeneous slip generator is used to forward model a suite of earthquake rupture scenarios on the Mentawai Segment of the Sunda Subduction Zone. Up to 1000 rupture models that fit constraints provided by coral and geodetic records of coseismic vertical deformation from major earthquakes in 1797, 1833 and 2007 are used to model inundation and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
(107 reference statements)
1
18
0
Order By: Relevance
“…The properties of the fault plane are consistent with the previous investigations. For instance, the depth is comparable with the source models of the past Mentawai-Sunda subduction earthquakes and the strike and dip angles are in line with the slab models of the Sunda subduction zone developed by the USGS (Newman et al, 2011;Satake et al, 2013;Philibosian et al, 2014;Yue et al, 2014;Hayes et al, 2009Hayes et al, , 2012. In addition, to stochastically generate the earthquake sources, the fault plane is divided into 10 km by 10 km sub-faults (see Fig.…”
Section: Earthquake Scenario Selectionsupporting
confidence: 78%
“…The properties of the fault plane are consistent with the previous investigations. For instance, the depth is comparable with the source models of the past Mentawai-Sunda subduction earthquakes and the strike and dip angles are in line with the slab models of the Sunda subduction zone developed by the USGS (Newman et al, 2011;Satake et al, 2013;Philibosian et al, 2014;Yue et al, 2014;Hayes et al, 2009Hayes et al, , 2012. In addition, to stochastically generate the earthquake sources, the fault plane is divided into 10 km by 10 km sub-faults (see Fig.…”
Section: Earthquake Scenario Selectionsupporting
confidence: 78%
“…Nevertheless, this is a point probably deserving further investigation, considering that Satake et al (2013) showed how inundation from the Tohoku 2011 tsunami was variably controlled by long-period offshore tsunami components on flat coastal plains and shorter-period peaks in steep coastal areas. Indeed, Gusman et al (2014) used two cycles of a tsunami for identifying similar waves. Conversely, since, as described in the next section, offshore wave comparison is not used anymore in the near-field, this issue will not apply for local sources.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry is essential to outlining the earthquake source zone, whilst a so-called asperity zone determines the areas of concentrated slips within the fault plane. In general, modeling an earthquake rupture process in terms of earthquake source and asperity zones for the future tsunamigenic earthquakes in the Mentawai-Sunda region is complicated and has significant uncertainty Griffin et al, 2016). In this study, the future earthquake source area in the Mentawai segment is defined using the fault rupture areas of the historical subduction earthquakes in the Sunda subduction zone (see Muhammad et al, 2016, for details).…”
Section: Earthquake Scenario Selectionmentioning
confidence: 99%
“…In addition, with the low-lying plain topographic features in Padang, the probability of large inundated areas and large inundation depths is also high (Borrero et al, 2006;Muhari et al, 2010Muhari et al, , 2011. In the past, two types of earthquake source scenarios have been mainly considered to develop tsunami risk mitigation plans in Padang: deterministic scenarios (Borrero et al, 2006;Schlurmann et al, 2010;Muhari et al, 2010Muhari et al, , 2011 and probabilistic scenarios (McCloskey et al, 2008;Griffin et al, 2016). These two methods have both advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation